Human and motivation - M. Yusof, Halimah (2015)
As researchers continue in their quest to find dynamics between human and motivation, this article intend to provide some reviews on the published works in human motivation. Motivation is a desire that elicits certain behaviour (Steers, Porter, & Bigley, 1996). It is an inner state or condition that gives direction by stimulating behavioural responses(McClelland, 1998). Although motivation has been defined in varieties of way, there are three qualities that are most often included in the definition; (a) it is an inner power, (b)it inspires action, and (c), it regulates action and behaviours (Russell, 1971). Over the years, various theories have emerged in relation to human and motivation. In this article, discussion was done on some of the most significant theories of motivations available over the years. Selective qualitative reviews on previous motivational theories, published researches, book chapters and special issues of journal on human and motivation were done. It can be concluded that motivation is an important attributes in human being, either for personal or work life. With motivation, human could achieve many tasks and goals that are important in life. Thus, it is believed that more research in human motivation should be done to foster stronger motivation in human that can benefit in increasing work performance and personal accomplishment. This article highlighted future directions that may promote our understanding on human motivation. This article only manages to review articles that are available online. Thus, this review is limited to the online availability of the resources.